Higher Triglyceride–Glucose Index Is Associated With Increased Likelihood of Kidney Stones - Qin, Zheng; Zhao, Junjie; Geng, Jiwen; Chang, Kaixi; Liao, Ruoxi; Su, Baihai (Frontiers in Endocrinology, 2021)
Aims: We aimed to assess the association between triglyceride glucose (TyG) index and kidney stones in US adults. Methods: Data was obtained from the 2007-2014 National Health and Nutrition Examination Survey (NHANES). Participants aged ≥ 18 years who were not pregnant and provided complete data about TyG index and kidney stones were included in analysis. Weighted multivariable regression analysis and subgroup analysis were preformed to estimate the independent relationship between TyG index with nephrolithiasis and recurrence. Results: A total of 20972 participants were included with the mean TyG index of 8.71 ± 0.72. The prevalence of nephrolithiasis and recurrence were 9.30% and 3.17% overall and increased with the higher TyG index tertiles (Nephrolithiasis: Tertile 1, 6.98%; Tertile 2, 9.15%; Tertile 3, 11.98%, p<0.01; Recurrence: Tertile 1, 1.84%, Tertile 2: 3.27%; Tertile 3: 4.50%, p<0.01). Each unit increase in TyG index was associated with 12% and 26% higher odds of nephrolithiasis (OR=1.12; 95%CI:1.02-1.22; p=0.02) and recurrence (OR=1.26; 95%CI: 1.08-1.46; p<0.01). Interaction tests indicated that no significant effect of gender, age, body mass index, hypertension and diabetes on this association between TyG index and kidney stones. Conclusions: Higher TyG index was associated with an increased likelihood of nephrolithiasis and recurrence. Considering TyG index is a reliable indicator of insulin resistance (IR), treatment and management of IR at a younger age may improve or alleviate the occurrence and recurrence of kidney stones.